Diary of a wimpy kid; The Last straw - Kinney,Jeff (Penguin, 2009)
The book, 'Diary of a Wimpy Kid – 3 The Last Straw' is a part of the book series - 'Diary of a Wimpy Kid' written by Jeff Kinney. The book series revolves around the kid Greg Heffley who is naughty, honest and charming in his own way.